Gelatin-Based and Gelatin-Free Electrospun Fibers of Lycopene/Cyclodextrin Inclusion Complexes with Potent Antioxidant Activity - Yildiz, Zehra Irem; Topuz, Fuat; Kilic, Mehmet Emin; Durgun, Engin; Uyar, Tamer (Amer Chemical Soc, 2024)
Lycopene, a carotenoid pigment in tomatoes, is used as a dietary supplement with antioxidant effects, but it is vulnerable to environmental factors, such as heat, oxygen, and light. Therefore, there is considerable interest in stabilizing such fragile molecules against environmental influences to preserve their bioactivity during processing and long-term storage. This paper reports the encapsulation and stabilization of lycopene within cyclodextrin (CD) fibers in the presence or absence of gelatin. The successful embedding of lycopene was confirmed by FTIR and NMR analyses. The lycopene's bioactivity could be preserved during processing via electrospinning and long-term storage by stabilizing it against environmental factors. The encapsulated lycopene showed remarkable antioxidant activity, improved thermal stability, and increased UV light stability. The hydrophilic nature of gelatin improved the dissolution of the resulting fibers in water, giving these fibers potential for rapid oral delivery of food-derived molecules encapsulated in fibers.
Keywords: lycopene; cyclodextrin; inclusion-complexation; electrospinning; antioxidantfibers